Pengaruh Lama Rebusan Daun Sirih terhadap Responsifitas Mastitis Sapi Perah - Serliana Mano; Stefanus Sio; Theresia I. Purwantiningsih (JAS, 2021)
Mastitis is udder inflammation caused by bacteria that entry through the teat. Economically, mastitis is very detrimental to farmers because it can reduce milk production. The purpose of this study is to provide an alternative teat dipping solution that is safe, inexpensive, and easily found by the farmers. The research was carried out from September to October 2019 at the Claretian Benlutu Monastery Ranch, South Central Timor. The method used in this study is a randomized block design (CRD) consisting of 4 treatments 3 replications so that there are 12 experimental units. The treatments given are as follows R0 = plain water, R1 = commercial antiseptic solution, R2 = betel leaf decoction 45 minutes and R3 = decoction of betel leaf 60 minutes. The variables observed in this study were the result of mastitis detection and milk acidity test (pH test). The results showed that betel leaf stew did not have a significant effect on the results of the California Mastitis Test and the acidity level (pH). It can be concluded that the betel leaf decoction has the same ability as a commercial antiseptic in preventing mastitis in dairy cattle at Claretian Benlutu Ranch.